Poly(vinylidene fluoride‐co‐hexafluoropropylene) nanocomposites incorporating cellulose nanocrystals with potential applications in lithium ion batteries. Issue 1 (27th April 2012) - Kelley, Jeremiah; Simonsen, John; Ding, Jie
Abstract Cellulose nanocrystals (CNCs) have received considerable attention recently because CNCs can be produced from renewable materials such as straw, wood, cotton, and sea animals (tunicates). CNCs are one of the stiffest organic materials, with an estimated tensile modulus (E) of 80–160 GPa depending on the starting material. In addition, composites incorporating CNCs have been fabricated from a variety of polymer matrices and CNCs have been shown to increase the E significantly and to a lesser extent the tensile strength (TS). A copolymer of poly(vinylidene fluoride) (PVDF), PVDF‐co‐hexafluoropropylene) (PVDFHFP), has received interest over the years in the area of lithium ion battery separator technology. However, the mechanical properties of neat PVDFHFP do not meet the necessary requirements for commercial separators, especially the low E. In this work, novel PVDHFHFP/CNC nanocomposite films were fabricated and characterized. It was found that incorporation of CNCs improves the E and TS. The improvement in mechanical properties of PVDFHFP upon addition of CNCs makes PVDFHFP a more suitable candidate for polymer separators in lithium ion batteries. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2012